Penggunaan Strategi Pembelajaran Everyone is Teacher Here untuk Meningkatkan Hasil Belajar IPA Siswa Kelas V SD - Saputra, Ardiko; Zuryanty, Zuryanty; Muhammadi, Muhammadi (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2015)
The purpose of this study was to describe using everyone is teacher here strategy to improving student learning outcomes in science learning in class v sdn 25 gadut tilatang kamang. This research is a classroom action research (PTK), using a qualitative and quantitative approach. The results showed an increase in: (a) Learning Planning in the first cycle obtained an average of 80% (B) increased in the second cycle to 96% (SB), (b) Learning Implementation aspects of the teacher the first cycle obtained an average the average is 79% (C) increased in the second cycle to 98% (SB) and the Learning Implementation aspects of the first cycle students get an average of 79,5% (C) increased in the second cycle to 96% (SB), (c) Learning outcomes of students in cycle I obtained an average of 76.8 (C) increased in the second cycle to 83.8 (B). From the results of the study it be concluded using everyone is teacher here strategy can improves the science learning outcomes of the fifth grade students of 25 Gadut Tilatang Kamang Elementary School Keywords : learning outcomes, everyone strategy